Comprensión lectora de textos en la educación intercultural bilingüe en estudiantes de 8 a 10 años - Quinlle Ilvis, Yessica Pamela (2020)
Reading comprehension is a fundamental part of the teaching-learning process, it involves the use of strategies that allow the student to understand a text in an integral way, that is, from its breakdown to its purpose, in addition to identifying the language used in its writing. The lack of this process within bilingual intercultural education is a factor that requires study. Thus, the objective ofthis research is to identify the influence of texts with intercultural relevance within basic education students………….